2005
DOI: 10.1086/431251
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Bar and Spiral Arm Strengths in Disk Galaxies

Abstract: The distribution of bar strengths in disk galaxies is a fundamental property of the galaxy population that has only begun to be explored. We have applied the bar-spiral separation method of Buta and coworkers to derive the distribution of maximum relative gravitational bar torques, Q b , for 147 spiral galaxies in the statistically welldefined Ohio State University Bright Galaxy Survey (OSUBGS) sample. Our goal is to examine the properties of bars as independently as possible of their associated spirals. We fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
152
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(174 citation statements)
references
References 68 publications
21
152
1
Order By: Relevance
“…Eskridge et al 2000;Block et al 2002;Buta et al 2005;MJ07;Laurikainen et al 2004Laurikainen et al , 2007. Thus, there are numerous complementary results that we can use or compare with.…”
Section: Osubsgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eskridge et al 2000;Block et al 2002;Buta et al 2005;MJ07;Laurikainen et al 2004Laurikainen et al , 2007. Thus, there are numerous complementary results that we can use or compare with.…”
Section: Osubsgsmentioning
confidence: 99%
“…In § 2, we define our complete sample of 143 bright (M B ≤ −19.3) low-to-moderately inclined (i ≤ 70 • ) spirals from the Ohio State University Bright Spiral Galaxy Survey (OSUBSGS; Eskridge et al 2002), which is widely used as the local reference sample for bright spirals by numerous studies (e.g., Eskridge et al 2000;Block et al 2002;Buta et al 2005;MJ07 ;Laurikainen et al 2004Laurikainen et al , 2007. In § 3, we perform 2D bulge-disk and bulge-disk-bar decompositions of H-band images using GALFIT (Peng et al 2002), and derive fractional light ratios (B/T , Bar/T , Disk/T ), as well as Sérsic indices and half light radii or scale lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods are adopted to determine these quantities. In particular, the bar strength can be measured using the gravitational torque exerted by the bar (Block et al 2002;Buta et al 2005), the maximum ellipticity of the bar (Martin 1995;Jogee et al 1999;Knapen et al 2000;Laine et al 2002;Marinova & Jogee 2007;Barazza et al 2008), Fourier decomposition (Elmegreen et al 1996), and visual estimates of strength (Eskridge et al 2002). As described in Sect.…”
Section: The Properties Of the Barsmentioning
confidence: 99%
“…By adopting this approach, strong bars were detected twice as frequently in near-infrared data than optical data (Eskridge et al 2000) and the bar fraction was found to increase between Sc galaxies and later types (Odewahn 1996). Apart from visual classification, a quantitative characterization of bars has been attempted using for instance, the gravitational torque method (Block et al 2002;Laurikainen et al 2002;Buta et al 2005), Fourier dissection Laurikainen et al 2006), and ellipse fits to the galaxy isophotes (Regan & Elmegreen 1997;Abraham et al 1999;Sheth et al 2000Sheth et al , 2002Sheth et al , 2008Knapen et al 2000;Erwin & Sparke 2002;Erwin 2005;Jogee et al 2002aJogee et al ,b, 2004Whyte et al 2002;Elmegreen et al 2004;Reese et al 2007;Menéndez-Delmestre et al 2007;Marinova & Jogee 2007;Barazza et al 2008). These methods provide measurements of the bar length and shape and enable the impact of the bar on the disk to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have estimated bar frequency from observations (Block et al 2002;Laurikainen et al 2004;Buta et al 2005) and, in the bar strength histogram, found a dearth of weak bars, with an extended wing of strong bars. In TC07, we estimated the bar frequency in a sample of pure stellar galaxy discs.…”
Section: Statistics Of Bar Frequencymentioning
confidence: 99%